Understanding the complex microenvironment in oral cancer: the contribution of the Faculty of Dentistry, University of Otago over the last 100 years. Issue 1 (2nd January 2020) - Rich, Alison Mary; Hussaini, Haizal Mohd; Seo, Benedict; Zain, Rosnah Bt
ABSTRACT: Malignant tumour cells, including malignant keratinocytes of oral squamous cell carcinoma (OSCC), exist in conjunction with other functional cells and it is well recognised that interaction between these groups of cells is important in tumour progression. In addition to cells (tumour cells, immune/inflammatory cells, fibroblasts, vascular and lymphatic endothelial cells, adipocytes) the tumour microenvironment (TME) comprises extracellular matrix and soluble factors, signalling molecules and metabolites such as enzymes, growth factors, cytokines, microRNAs and microvesicles. Our Oral Molecular and Immunopathology Research Group has explored and examined the interactions of the immune network involved in the TME such as tumour infiltrating lymphocytes (TILs), regulatory T cells (Tregs), antigen presenting cells (APCs), associated cytokines such as IL17, IL22, IL23 and other current potential anti-cancer targets such as ER stress and exosomes. This paper will provide an overview of the history of OSCC research at the University of Otago, as well as elaborate current understanding of the TME in OSCC, based on ongoing research undertaken in the Oral Molecular and Immunopathology Research Group of the Sir John Walsh Research Institute at the Faculty of Dentistry, University of Otago.